RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN PEDAGOGIK BAGI GURU IPA SMP - Fitriani, Annisa; Natalina L, Mariani; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aim to design a prototipe workbook of Pedagogical Knowledge (PK) for strengthening Natural Science Teacher Competencies. The research procedures are : Analyze, Design, and Development. The book was developed based on essential indicator of Teacher Competency Test 2015 and essential indicator of PCK test 2016 on pedagogy aspek. Analyze, design, develop, first simulation and validation of workbook by internal validator conducted at the Laboratory of Biology Education FKIP University of Riau. External validation, second simulation and user response of the workbook in MGMP IPA Pekanbaru. Workbooks validated on four aspects include format; illustrations; language, and content. Validated workbook will be disseminate after revised. The workbook has valid category and can be used as a learning resource by the teachers to strengthening of Pedagogical Knowledge (PK) Natural Science Teacher.Keywords: Workbook, Pedagogical Knowledge, Natural Science Teacher